The Mystery of Collective Intelligence - White, George (Ethics International Press Limited, 2022)
"Why are some teams, businesses, countries and cultures successful and enduring, and some not? The book describes practical applications of collective intelligence, and unlocks the secrets of highly successful teams at all levels in corporations and governments. Well-known companies are analysed, and the reasons for their success or decline explained.The Mystery of Collective Intelligence proposes a new theory of organizational intelligence, explaining how organizational intelligence lies behind AI, robotics and the accelerating automation that is revolutionizing industry around the world. The book explains how organizations themselves can improve their decision-making cultures.The Mystery of Collective Intelligence describes the scientific basis for collective decision-making, and discusses how ethical and socially responsible corporate objectives lead to increased innovation and information sharing, which ultimately leads to improved economic success.".